Artificial intelligence competencies of vocational teachers using for the design of learning activities - Rattanakha, Raweewarn; Hinon, Kanitta; Wannapiroon, Panita; Wannapiroon, Naphong; Jitsupa, Jira; Sookpreedee, Nipone (Institute of Advanced Engineering and Science, 2025)
Currently, information technology used in teaching and learning management is constantly evolving. Therefore, the development of vocational teachers’ artificial intelligence competencies (AIC) of vocational teachers using artificial intelligence (AI) for the design of learning activities using questions is to develop the ability to use information technology in teaching and learning management with an emphasis on the use of AI for education. Teachers in the college received practical training on the application of AI in teaching and learning management. In using AI, which creates knowledge and understanding for teachers, it can be applied in the design of learning activities. From allowing teachers to practice, this has a positive effect on the increase in AI skills of teachers from before attending the training. Overall, vocational teachers have a great level of AIC; the average score is 21.72 points and from the assessment of overall satisfaction at the highest level. The training content is suitable for the current situation. The knowledge gained can be used to benefit in organizing teaching activities. The speakers have interesting teaching techniques.